Forrageio de operárias de Tetragonisca fiebrigi (Apidae; Meliponini) : potencial de obtenção de recursos e polinização - Kaehler, Tatiana Guterres (2017)
In bees, foraging flight can influence spatial characteristics of interactions in the community, which have consequences at ecosystem levels, such as nutrient transfer, seed dispersal and pollination. The pollination service performed by bees, in addition to influencing plant reproduction, positively affects about 90% of 107 global crops. One of the fundamental components for understanding populations persistence and interactions among species is the bees' foraging ranges, which can be determinant for population dynamics, genetic structure and life history. Considering this, the present work aims to analyze the foraging of Tetragonisca fiebrigi (Schwarz, 19838) using artificial feeders. In addition to determining the flight distance for the specie, the workers' space-time learning to the feeder is evaluated, the relation between the visitation rate and the quality of the food resources offered and the influence of the meteorological factors on the foraging. The experiments were carried out in the Botanical Garden of Porto Alegre, RS, Brazil, from December 2014 to April 2015 and from November to December 2016. To analyze bees’ learning in relation to the feeder, during two days the resource was available at the entrance of the colony and the number of visiting workers was counted every 1 hour. Also, the influence of the meteorological factors in relation to the maximum distance reached by the workers was analyzed along with the relation to the visitation rate in the artificial feeder. In order to analyze the flight distance of the species, the feeder was arranged near the entrance of the hive and, from the bees’ visitation, was moved every 30 min by 30m, 50m, 100m, 150m and so on until the maximum distance with foraging of workers. Five feeders containing sucrose solutions with different concentrations (10, 20, 30, 40, 50%) were simultaneously placed in front of each target colony to analyze the relationship between the quality of the resource and the visitation rate. These feeders were spaced apart at 10 m intervals and the number of visits counted at each distance for 30 min. The results showed that T. fiebrigi reached a forage distance of 600 m in the feeder. However, the number of visits decreased as the distance from the resource increased relatively to the colony. The sugar concentration in the syrup offered have influenced the workers’ decision-making, that is, the quality of the resources was directly related to the visitation rate, since the workers increased visitation frequency at the highest concentrations, from 30 to 50%. At lower concentrations, 10 and 20%, the number of visits was lower and the workers stopped the foraging in a distance closer to the colony (80 m). Regarding the learning of the bees to locate the feeder, there was a visitation rate increase on subsequent days of availability of the resource. This study made it possible to relate visitation rate in relation to flight distance, meteorological factors and resource quality, enriching the understanding of the foraging pattern of T. friebrigi. Knowledge about the foraging of this species, as well as other bee species, allows inferences about migration, colonization, resource collection, pollination potential and the application of this information for management aimed at biodiversity conservation. In meliponiculture, this knowledge allows the spatial planning of the colonies according to the distribution and abundance of the resources present in the landscape. Similarly, knowledge about the foraging of bees is important in agriculture, due to the possibility of landscape planning, or even directed pollination, to increase the productivity of the crops dependent on those pollinators.